1981
DOI: 10.1073/pnas.78.1.328
|View full text |Cite
|
Sign up to set email alerts
|

Growth regulation, reverse transformation, and adaptability of 3T3 cells in decreased Mg 2+ concentration

Abstract: A nontransformed and a spontaneously transformed clone of BALB/c 3T3 cells were compared for their capacity to multiply in decreased concentrations of Mg2e. Cells of the nontransformed clone were flat, formed regularly patterned, nonoverlapping arrays, required high serum concentration for multiplication, had a low saturation density, and did not make colonies in agar. Cells of the transformed clone were slender and spiky, formed random, overlapping arrays, multiplied in low serum concentrations, and had no fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…It has been reported that magnesium deprivation reduces DNA, RNA, and protein synthesis in chicken fibroblasts (Rubin, 1979, and restores both normal appearances and growth regulation in spontaneously transformed BALB/c 3T3 cells (Rubin, 1981). Magnesium specifically regulates adenylate cyclase activity in numerous cells and species (Cech et al, 1980) and enhances insulin-dependent stimulation of cyclic AMP phosphodiesterase in adipocytes (Ueda et al, 1984).…”
mentioning
confidence: 97%
“…It has been reported that magnesium deprivation reduces DNA, RNA, and protein synthesis in chicken fibroblasts (Rubin, 1979, and restores both normal appearances and growth regulation in spontaneously transformed BALB/c 3T3 cells (Rubin, 1981). Magnesium specifically regulates adenylate cyclase activity in numerous cells and species (Cech et al, 1980) and enhances insulin-dependent stimulation of cyclic AMP phosphodiesterase in adipocytes (Ueda et al, 1984).…”
mentioning
confidence: 97%
“…As compared to their normal counterpart, several neoplastic cells may nevertheless exhibit higher levels of intracellular Mg [Rubin, 1982a]. Furthermore, it has been described that spontaneously or virus transformed fibroblasts and other cells grown under Mg restriction may rapidly assume mor-phological and functional characteristics of differentiated cells [Rubin, 1981[Rubin, , 1982bMcKeehan et al, 1978;Hoftiezer et al, 1985]. Dietary restriction of Mg and cell Mg deficiency have also been shown to accelerate aging both in vivo and in vitro [Gü nther, 1991;Costello et al, 1992;Calviello et al, 1993].…”
mentioning
confidence: 99%
“…The spontaneously transformed clone (clone 14) and the flat, nontransformed clone (clone 2) were isolated as described (Rubin, 1981). Cells were maintained in MCDB 402 medium with 10% calf serum.…”
Section: Materials and Methods Cells And Culture Methodsmentioning
confidence: 99%
“…The subsequent procedure for determining the rate of thymidine incorporation has been described (Rubin, 1981).…”
Section: Thymidine Incorporationmentioning
confidence: 99%